The concept of muhammadiyah education renewal towards opportunities and challenges in the modern era - Rifqi Achsanul Kholqi Alfarisi; Zainuddin Syarif (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This research aims to comprehensively analyze the opportunities and challenges of the concept of Muhammadiyah education reform in responding to changes triggered by digital transformation, globalization, and socio-cultural dynamics of contemporary Indonesian society. To achieve this goal, this study uses a qualitative approach by combining content analysis and Critical Discourse Analysis (CDA) Fairclough model. The data was obtained through the study of official Muhammadiyah documents, such as the Tanfidz Muktamar, the AIK-ISMUBA curriculum guidelines, the policies of the Dikdasmen Council, and the scientific literature indexed by Sinta and Scopus for the 2020–2025 period. The results of the study show that there are a number of strategic opportunities for strengthening the concept of Muhammadiyah education reform, including the optimization of the ISMUBA curriculum as an integrative framework for Islamic values and competencies in the 21st century, the development of a digital learning ecosystem based on blended and hybrid learning, increasing the digital literacy of teachers and students, and strengthening international networks through the internationalization program of PTMA. This opportunity affirms Muhammadiyah's position as a pioneer of modern Islamic education that is adaptive to technological developments and remains rooted in religious values. However, this study also identifies various structural, pedagogical, and cultural challenges, such as quality disparities between schools, low pedagogical-technological competence of some teachers, weak internalization of AIK values in school culture, funding inequality, and global popular culture penetration that affect students' religious identities. The conclusion of the study emphasizes that the reform of Muhammadiyah education is an ideological as well as a technical process that requires strengthening governance, teacher professionalism, research culture, and institutional capacity. Practical recommendations are presented to encourage more adaptive, measurable, and transformative renewal strategies.